Vida feliz na filosofia de Santo Agostinho - Souza, Josemar Jeremias Bandeira de (2006)
Based on a little text by Saint Augustine, named De Beata Vita, written during a cultural retreat in 388 B.C., this paper aimed at comprehending the reasons that drive the mankind, in a universal attitude, to seek a happy life, as well as understanding the ways proposed by Augustine to reach what is, according to himself, the only purpose for which people think philosophically (Conf. I, I, 1). It was possible to verify, then, that the Bishop of Hippo, entirely submissive to Christian faith and under great influence of the eudemonistic Greeck tradition, developed a practica, fundamentally ethical and moral philosophy, which, by exalting virtue and disengaging from merely temporal values, sought happiness in what was not perishable. For all that is subject to time may have its nature corrupted by the evil, which, in his comprehension, is the lack or distortion of what is good. Acknowledging then that only God is eternal and not subject to time, and that He could not be lost or modified, Augustine inferred that seeking happiness was, inevitably, seeking God. However, he knew that men could not reach God by their own effort, given that He is infinite. So, some divine helpe becomes necessary: grace. At this point, Augustine separated from the Greek, as he substituted human knowledge whith divine knowledge. Thus, without abandoning intelligible comprehensio, necessary for recognizing what coud be called beata vita, he tries, through conscience experience and auto comprehension, to find spiritual plenitude, in which would be perfect Truth and true freedom, without which living true happiness would be impossible.